The Importance of Tacit Knowledge in Geoscience Brought to the Surface through Artistic Methods - Manley, Nicole A. L. (Art/Research International, 2022)
This study of scientists’ reactions to the experience of an art exhibition, researches Polyani’s (2009) tacit knowing, a knowledge that we cannot easily express into words, and Deleuze and Guattari’s (1987) striated and smooth spaces, with striated being a channelled and restricted way of thinking compared to smooth as free flowing and creative. To research these concepts, a psycho-social method—the Visual Matrix (VM)—is used as a research method. Two groups of geoscientists were brought together to first view Waterways, an art exhibition, and then participate in a VM. The research concludes that the scientists were able to express tacit knowledge elicited through the experience of Waterways, enabling them to think differently about their work and form new understandings about the natural environment in relationship to themselves and society. For artists, the VM can be an effective tool when working with scientists and the public. The study argues the importance of bringing tacit knowledge to the surface, allowing greater possibility of combining scientific and artistic approaches.